The buoyancy force and flow acceleration effects of supercritical CO2 on the turbulent heat transfer characteristics in heated vertical helically coiled tube - Zhang, Shijie; Xu, Xiaoxiao; Liu, Chao; Zhang, Yadong; Dang, Chaobin (International Journal of Heat and Mass Transfer, 2018)
•The buoyancy parameter ϕ2 is proposed to quantified analysis buoyancy effect.•Flow acceleration plays a role in the heat transfer deterioration at q+ > 4.5 × 10−4.•The buoyancy factor Fb and acceleration factor Fac are proposed.•A new correlation is proposed for supercritical CO2 in helically coiled tube. Numerical simulations are performed to investigate the turbulent heat transfer characteristics of supercritical CO2 in heated vertical helically coiled tube, and primary focus is to analyze the mechanism of buoyancy force and flow acceleration on the heat transfer. The results show similar effect from buoyancy force and centrifugal force, and both forces induce a secondary flow in the cross section that improves the heat transfer efficiency. The buoyancy parameter ϕ2 and flow acceleration parameter q+ are established with reasonably good validation against numerical results. On the basis of the two parameters, the buoyancy factor Fb and the acceleration factor FAc are proposed to quantify buoyancy and flow acceleration effect, respectively. Furthermore, a temperature difference correction factor Ft is introduced to consider variation of thermo-physical properties. A new semi-empirical heat transfer correlation is proposed for supercritical CO2 in function of Fb, FAc and Ft for the vertical helically coiled tube.